Composite phase change electrolyte and preparation method and application thereof

By designing a composite phase change electrolyte, the performance and safety issues of lithium batteries under high and low temperature environments have been solved, achieving efficient battery operation and safety protection over a wide temperature range.

CN120834276APending Publication Date: 2025-10-24NINGBO UNIV

Patent Information

Application Number
CN202511063134.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-10-24

AI Technical Summary

Technical Problem

Existing lithium battery electrolytes present a contradiction in balancing high ionic conductivity, wide temperature adaptability, and thermal runaway suppression capabilities, making it difficult to simultaneously meet the requirements for low-temperature operation and high-temperature safety protection.

Method used

A composite phase change electrolyte is used, which contains lithium salt, solvent, crosslinking agent and inorganic nanoparticles. It forms a solid at high temperature through crosslinking reaction, blocking the ion pathway and achieving battery safety protection.

Benefits of technology

It maintains high ionic conductivity at room temperature, preserves battery performance at low temperature, and blocks ion pathways at high temperature to prevent thermal runaway and ensure battery safety.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and relates to a composite phase change electrolyte and a preparation method and application thereof. The composite phase-change electrolyte comprises a lithium salt, a solvent, a cross-linking agent and inorganic nanoparticles, and the cross-linking agent is one or more of a polysiloxane derivative and a polyfunctional group acrylate derivative. According to the composite phase change electrolyte provided by the invention, relatively high ionic conductivity is provided, the ion diffusion resistance is reduced, and the electrolyte is always kept in a liquid state within a conventional temperature range; when the battery reaches the phase change temperature, the electrolyte is changed from liquid to solid, an ion path is blocked, and the safety protection of the battery at high temperature is realized; in addition, the battery using the composite phase change electrolyte has a relatively long cycle life at a room temperature and in a working environment of-30 DEG C. The composite phase-change electrolyte is suitable for a high-safety lithium ion battery, and is especially suitable for application scenes of extreme temperature conditions, such as high-temperature thermal runaway protection and low-temperature performance protection.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of batteries, and relates to a composite phase change type electrolyte as well as a preparation method and application thereof. BACKGROUND

[0002] Under the background of rapid development of sustainable energy, lithium ion batteries have been widely used in electric vehicles, portable electronic devices and grid energy storage due to their high energy density, excellent cycle performance and long service life. As a core component of lithium batteries, electrolyte is usually composed of organic solvents, lithium salts and additives, and its main function is to provide a reversible lithium ion transmission channel between the positive and negative electrodes. The performance of electrolyte directly affects the capacity, rate performance, cycle life and safety of lithium batteries. Electrolyte with poor chemical stability is easy to decompose, producing flammable gases such as hydrogen, which causes battery capacity attenuation, shortens the service life, and even causes explosion. When the thermal stability of electrolyte is insufficient, the accumulation of heat in the battery due to abnormal working conditions such as overcharge and short circuit, electrolyte decomposition will release a large amount of heat, triggering a vicious cycle of "thermal decomposition-heat generation-temperature rise-further decomposition", which eventually leads to thermal runaway. The flash point of some solvents in electrolyte is low and easy to burn, and the high-temperature decomposition of lithium salt will also generate flammable gas, increasing the safety risk.

[0003] Some existing technologies improve battery performance by designing phase change electrolyte, for example, patent CN113258134A discloses an organic phase change electrolyte and its application, wherein the organic phase change electrolyte includes lithium salt and solvent, and the organic phase change electrolyte has a phase change temperature of solid-liquid transition. During the charging process, the organic phase change electrolyte can be converted into liquid state by controlling the temperature, and since the liquid electrolyte has high conductivity, it can realize fast charging of the battery; during the discharging process, the organic phase change electrolyte can be converted into solid state by controlling the temperature, and the solid electrolyte can effectively inhibit the dissolution of the positive electrode material during the discharging process, thereby improving the cycle performance of the battery. However, the battery has poor performance when working in a low-temperature environment, and it has the problem of phase change reversibility, and cannot inhibit thermal runaway.

[0004] Some other studies improve safety by adding flame retardants or thermally responsive polymers, but there are risks of side reactions of flame retardants or insufficient temperature control precision of thermally responsive polymers, which leads to the problem of difficult accurate control of phase change temperature.

[0005] The current electrolyte technology has significant contradictions in balancing "high ionic conductivity", "wide temperature adaptability" and "thermal runaway inhibition ability": traditional liquid electrolyte has high conductivity, but has insufficient thermal stability and safety; the flame retardant system or thermally responsive polymer improves some safety performance, but it is difficult to meet the requirements of low-temperature working demand and high-temperature irreversible blocking at the same time. Developing an electrolyte system with wide temperature ion conduction ability and thermal runaway prevention function has become a key technical difficulty to break through the safety bottleneck of lithium batteries. SUMMARY

[0006] To solve the above problems in the prior art, the purpose of the present application is to provide a composite phase change type electrolyte and its preparation method and application to overcome the shortcomings of the prior art. The present application adopts the following technical solutions to achieve the purpose of the application:

[0007] The first aspect of the present application provides a composite phase change type electrolyte, comprising a lithium salt, a solvent, a crosslinking agent, and inorganic nanoparticles; the addition amount of the crosslinking agent and the inorganic nanoparticles is respectively 0.1-10wt% of the total amount of the electrolyte.

[0008] The crosslinking agent is one or more of polysiloxane derivatives and multifunctional acrylate derivatives.

[0009] Preferably, the polysiloxane derivative is one or more of polydimethylsiloxane (PDMS), polymethylvinylsiloxane (PVMS), and polymethylphenylsiloxane (PMPS).

[0010] The multifunctional acrylate derivative is pentaerythritol tetraacrylate (PETTA) or polyethylene glycol diacrylate (PEGDA).

[0011] Preferably, the addition amount of the crosslinking agent is 0.5-5wt% of the total amount of the electrolyte.

[0012] Preferably, the inorganic nanoparticles are one or more of silicon dioxide, titanium dioxide, zinc oxide, zirconium oxide, magnesium oxide, and niobium dioxide.

[0013] Further preferably, the crosslinking agent is polyethylene glycol diacrylate, and the inorganic nanoparticles are silicon dioxide. This combination forms an electrolyte applied to a battery, which has better capacity retention at room temperature and low temperature.

[0014] Preferably, the average particle size of the inorganic nanoparticles is 1-999nm, further preferably 5-500nm, and still further preferably 10-300nm.

[0015] Preferably, the addition amount of the inorganic nanoparticles is 0.5-5wt% of the total amount of the electrolyte.

[0016] Further preferably, the crosslinking agent is polyethylene glycol diacrylate, and the inorganic nanoparticles are silicon dioxide. When the crosslinking agent is polyethylene glycol diacrylate and the inorganic nanoparticles are silicon dioxide, the electrolyte has excellent ionic conductivity, and the battery prepared from the electrolyte has excellent capacity retention.

[0017] The lithium salt dissolved in the lithium battery electrolyte provides lithium ions for the battery. During the charging and discharging process of the battery, the lithium salt dissociates and releases lithium ions. Lithium ions migrate back and forth between the positive and negative electrodes, realizing the charge storage and release of the battery. Preferably, the lithium salt is one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium difluoro(oxalato)borate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(fluorosulfonyl)imide (LiFSI).

[0018] Preferably, the concentration of lithium salt in the electrolyte is 0.1-5 mol / L, and further preferably 0.5-3 mol / L.

[0019] The solvent in the electrolyte is used to dissolve solutes such as lithium salt to form a type of organic solvent or mixed solvent with good ionic conductivity. The main function of the solvent is to provide an ion transport medium, so that the lithium salt can fully dissociate in it to form freely moving lithium ions, thereby realizing the rapid transport of lithium ions between the positive and negative electrodes during the charging and discharging process of the battery, and ensuring the normal operation of the battery. Preferably, the solvent is one or more of carbonate solvents and ether solvents. The carbonate solvents can be one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). The ether solvents can be one or more of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGME), and tetrahydrofuran (THF).

[0020] Preferably, the electrolyte further includes an additive, which is one or more of ethyl acetate (EA), methyl propionate (MP), fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl sulfate (DTD), and 1,3-propane sultone (PS).

[0021] Preferably, the additive is added in an amount of 0.1-5 wt% of the total amount of the electrolyte. Further preferably, it is 0.2-3 wt%.

[0022] Preferably, the ionic conductivity of the electrolyte in the liquid state is 4*10 -3 ~ 5*10 -2 Scm -1 .

[0023] Preferably, the phase transition temperature of the electrolyte is 140-180℃. Under the trigger of the phase transition temperature, the electrolyte changes from a liquid to a solid state, the viscosity of the electrolyte is >1000 Pa·s, and the ionic conductivity is <0.01 mS cm -1 .

[0024] The electrolyte of the present application comprises a cross-linking agent and inorganic nanoparticles at the same time, the cross-linking agent helps to form a uniform solid electrolyte interface film, improves the charge and discharge efficiency and cycle performance of the battery, the inorganic nanoparticles are uniformly dispersed in the electrolyte and adsorbed on the electrode surface, which improves the roughness and chemical activity of the electrode surface, promotes the uniform transmission of lithium ions, and at the same time, enhances the mechanical stability and corrosion resistance of the electrode. The cross-linking agent reacts with the inorganic nanoparticles under thermal triggering to form a three-dimensional network, thereby causing the phase change of the electrolyte from liquid to solid, which can to some extent inhibit the safety problems such as short circuit and thermal runaway inside the battery.

[0025] The second aspect of the present application provides a preparation method of a composite phase change type electrolyte, comprising the following steps:

[0026] The lithium salt is added to the solvent, and stirred and mixed for 0.5-10 h until the solid is dissolved; then the cross-linking agent and inorganic nanoparticles are added and stirred and mixed for 0.5-10 h; and the electrolyte is obtained by filtration.

[0027] When the electrolyte contains an additive, the preparation method comprises: adding the lithium salt and the additive to the solvent, stirring and mixing for 0.5-10 h until the solid is dissolved; then adding the cross-linking agent and inorganic nanoparticles, stirring and mixing for 0.5-10 h; and filtering to obtain the electrolyte.

[0028] The third aspect of the present application provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the electrolyte is the above-mentioned composite phase change type electrolyte.

[0029] Preferably, the positive electrode sheet comprises a current collector and a positive electrode material on the current collector; the positive electrode material comprises a positive electrode active material, a binder and a conductive agent.

[0030] Preferably, the ratio of the positive electrode material comprises: 70-99wt% of the positive electrode active material, 0.5-10wt% of the binder and 0.5-20wt% of the conductive agent.

[0031] The positive electrode active material includes but is not limited to one or more of lithium iron phosphate (LFP), lithium cobaltate (LCO), lithium manganate (LMO), ternary lithium (NCA / NCM), lithium-sulfur (Li-S) and the like.

[0032] Preferably, the negative electrode sheet comprises a current collector and a negative electrode material on the current collector; the negative electrode material comprises a negative electrode active material, a binder and a conductive agent.

[0033] Preferably, the ratio of the negative electrode material comprises: 70-99wt% of the negative electrode active material, 0.5-10wt% of the binder and 0.5-20wt% of the conductive agent.

[0034] The negative active material includes but is not limited to one or more of graphite, soft carbon, hard carbon, silicon-based, lithium titanate, titanium niobate, etc.

[0035] Among the positive electrode and the negative electrode, the binder includes but is not limited to one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), guar gum (GG), sodium alginate (SA), polyacrylic acid (PAA), and chitosan, etc.; the conductive agent includes but is not limited to one or more of acetylene black (super P), carbon nanotubes, graphene, etc.

[0036] The lithium ion battery prepared includes but is not limited to a cylindrical type, a square shell type, a soft package type, or a button type, etc.

[0037] Preferably, the lithium ion battery has a capacity retention rate of ≥80% after 1000 cycles at 25°C under the condition of a rate of 1C, and a capacity retention rate of ≥20% after 1000 cycles at-30°C under the condition of a rate of 1C.

[0038] The fourth aspect of the present application provides a preparation method of a lithium ion battery, including the following steps:

[0039] S1, stirring the positive active material, the binder, and the conductive agent in a solvent until uniform to obtain a positive electrode slurry; stirring the negative active material, the binder, and the conductive agent in a solvent until uniform to obtain a negative electrode slurry; uniformly coating the positive electrode slurry and the negative electrode slurry on the current collector respectively, and then drying, rolling, and cutting to obtain a positive electrode sheet and a negative electrode sheet;

[0040] S2, assembling the prepared positive electrode sheet and negative electrode sheet with a diaphragm into an electric core, injecting the above-mentioned composite phase change type electrolyte, and then completing packaging to obtain a lithium ion battery.

[0041] Compared with the prior art, the present application has the following beneficial effects:

[0042] 1. The composite phase change type electrolyte provided by the present application provides high ionic conductivity, reduces ion diffusion resistance, keeps the electrolyte in a liquid state within a conventional temperature range, does not affect the normal operation of the battery, and has good cycle life when applied to a lithium ion battery.

[0043] 2. The composite phase change type electrolyte provided by the present application has a phase change temperature. When the battery reaches a phase change temperature of 140-180°C, the electrolyte changes from a liquid to a solid under the trigger of the phase change temperature, and the phase change is irreversible, thereby blocking the ion path and achieving safety protection of the battery at high temperature.

[0044] 3. The composite phase change type electrolyte provided by the present application can ensure the cycle life of the battery under a working environment of-30°C, breaking through the limitations of the prior art.

[0045] 4、The lithium ion battery prepared by using the composite phase change type electrolyte as the electrolyte in the application can be used for high temperature, short circuit or needle puncture safety experiments, and after the experiments, the internal electrolyte can be solidified and irreversible, the ion path is blocked, and the battery is disabled, so that the safety problems such as explosion and spread of toxic smoke are avoided.

[0046] 5、The electrolyte system with the temperature triggered irreversible phase change characteristic provided by the application is suitable for high safety lithium ion batteries, and is especially suitable for application scenes of extreme temperature conditions, such as high temperature thermal runaway protection and low temperature performance protection. DETAILED DESCRIPTION

[0047] In the description of the application, unless otherwise specified, the numerical range "a~b" represents a brief representation of any real combination between a and b, and a and b are included.

[0048] The plurality in the present application includes two, three, four, five or more.

[0049] The technical solutions of the application are further described and explained below through specific examples, and it should be understood that the specific examples described herein are only used to help understand the application, and are not used to limit the application. If not otherwise specified, the raw materials used in the examples of the application are all commonly used raw materials in the art, and the methods used in the examples are all conventional methods in the art.

[0050] In the following examples and comparative examples, the sources of the raw materials are as follows:

[0051] PDMS: Mcmaster-Carr, D849784;

[0052] PEGDA: Merck, 455008;

[0053] PETTA: Guangdong Yuhexin Material Co., Ltd.;

[0054] Nano-SiO2: Mcmaster-Carr, S817567, 15+5nm;

[0055] Nano-TiO2: Merck, 799289-500MG, 25nm.

[0056] Example 1

[0057] The phase change electrolyte provided in the example is composed of the following components:

[0058] Lithium salt: 2mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1 to form, crosslinking agent: 2wt% polydimethylsiloxane (PDMS), 2wt% SiO2 nanoparticles.

[0059] The preparation method of the phase change electrolyte is as follows: in an anhydrous and oxygen-free glove box, 10 ml of liquid EC is first taken by a pipette into a 50 ml glass vial, and then 10 ml of DMC is added, and the mixture is uniformly stirred at 300 rpm. Subsequently, an appropriate amount of LiPF6 is weighed and slowly added into the above-mentioned mixed solvent, and the stirring is continued for 6 hours under magnetic stirring to make LiPF6 completely dissolved to form a uniform and clear solution. Then, an appropriate amount of PDMS and SiO2 nanoparticles are sequentially added, and the mechanical stirring is continued for 4 hours to ensure that the components are fully and uniformly dispersed. Finally, the initial filtration is performed using a filter with a pore size of 1 μm to remove large particle impurities, and then the fine filtration is performed using a precision filter with a pore size of 0.1 μm to obtain a pure phase change electrolyte.

[0060] The ionic conductivity of the phase change electrolyte of the present embodiment is 5 x 10 -3 S cm -1 When heated to 160°C, the viscosity of the electrolyte increases sharply (>1000 Pa s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the Li + transport.

[0061] The present phase change electrolyte is used in a button lithium battery with lithium iron phosphate as the positive electrode. The positive electrode sheet is prepared by uniformly mixing lithium iron phosphate material, super P conductive agent and polyvinylidene fluoride in a ratio of 98:1:1 in N-methyl pyrrolidone (NMP), coating on an aluminum foil and drying at 80°C under vacuum. The negative electrode sheet is prepared by uniformly mixing graphite material, super P conductive agent and polyvinylidene fluoride in a ratio of 98:1:1 in NMP, coating on a copper foil and drying at 80°C under vacuum. The battery assembly is carried out under argon protection in a glove box, and the positive electrode sheet, the negative electrode sheet and the separator are assembled into a battery cell by the lamination method. The amount of the phase change electrolyte added is 15% of the total weight, and the design capacity of the assembled battery is 5 Ah.

[0062] After standing and formation, the test battery capacity is 5 Ah. After 1000 cycles at room temperature (25°C) at a rate of 1C, the capacity retention rate is still 80.2%. After 1000 cycles at -30°C at a rate of 1C, the capacity retention rate is 20.21%.

[0063] When the phase change electrolyte of the present embodiment is applied to a lithium ion battery, the temperature inside and outside the battery does not exceed 100°C during the charging and discharging processes; by controlling the external temperature to reach 160°C (phase change temperature), the electrolyte changes from a liquid state to a solid state, i.e., the crosslinking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the Li +During the needle penetration test, as the temperature of the punctured area rises rapidly, the local electrolyte also changes from liquid to solid, preventing the spread of heat diffusion.

[0064] Example 2

[0065] This embodiment provides a phase change electrolyte composed of the following components:

[0066] Lithium salt: 2 mol / L LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1, crosslinker: 2 wt% polyethylene glycol diacrylate (PEGDA), 2 wt% TiO2 nanoparticles.

[0067] The preparation method of the phase change electrolyte is the same as that in Example 1.

[0068] The ionic conductivity of the phase change electrolyte in this embodiment is 1.6×10 -2 S cm -1 When heated to 150°C, the electrolyte viscosity increases sharply (>1000 Pa·s) and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking Li + transmission.

[0069] The phase change electrolyte is used in a button-type lithium battery with lithium iron phosphate as the positive electrode. The preparation method of the battery is the same as that of Example 1.

[0070] After resting and forming, the battery's capacity was tested to be 5Ah. After 1000 cycles at a 1C rate at room temperature (25°C), the battery retained 95.3% of its capacity. After 1000 cycles at a 1C rate at -30°C, the capacity retention was 58.67%.

[0071] When the phase-change electrolyte of this embodiment is applied to a lithium-ion battery, the temperature inside and outside the battery does not exceed 100°C during charging and discharging. When the external temperature is controlled to reach 150°C (phase-change temperature), the electrolyte changes from liquid to solid, i.e., the cross-linking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity drops to <0.01 mS cm -1 , completely blocking Li + During the needle penetration test, as the temperature of the punctured area rises rapidly, the local electrolyte also changes from liquid to solid, preventing the spread of heat diffusion.

[0072] Example 3

[0073] This embodiment provides a phase change electrolyte composed of the following components:

[0074] Lithium salt: 2 mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1, cross-linking agent: 2wt% polyethylene glycol diacrylate (PEGDA), 2wt% SiO2 nanoparticles.

[0075] The preparation method of the phase change electrolyte is the same as that in Example 1.

[0076] The ionic conductivity of the phase change electrolyte of this example is 2.2 x 10 -2 S cm -1 When heated to 150℃, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking Li + transport.

[0077] The phase change electrolyte is used in a button lithium battery with lithium iron phosphate as the positive electrode, and the preparation method of the battery is the same as that in Example 1.

[0078] After standing and formation, the test battery capacity is 5 Ah. After 1000 cycles at room temperature (25℃) at a rate of 1C, the capacity retention rate is still 97.86%. After 1000 cycles at -30℃ at a rate of 1C, the capacity retention rate is 62.10%.

[0079] When the phase change electrolyte of this example is applied to a lithium ion battery, the internal and external temperatures of the battery do not exceed 100℃ during charging and discharging; by controlling the external temperature to 150℃ (phase change temperature), the electrolyte changes from a liquid state to a solid state, i.e., the cross-linking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking Li + transport, thereby effectively preventing safety problems of the battery. During the needle puncture experiment, the temperature of the punctured part rises rapidly, and the local electrolyte also changes from a liquid state to a solid state, preventing the spread of heat diffusion.

[0080] Example 4

[0081] The phase change electrolyte provided in this example is composed of the following components:

[0082] Lithium salt: 2 mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1, cross-linking agent: 2wt% pentaerythritol tetraacrylate (PETTA), 2wt% SiO2 nanoparticles.

[0083] The preparation method of the phase change electrolyte is the same as that in Example 1.

[0084] The ionic conductivity of the phase change electrolyte in the liquid state in this example is 1.2 x 10 -2 S cm -1 When heated to 150℃, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the transmission of Li + .

[0085] The phase change electrolyte is used in a button lithium battery with lithium iron phosphate as the positive electrode, and the preparation method of the battery is the same as that in Example 1.

[0086] After standing and formation, the capacity of the test battery is 5 Ah. After 1000 cycles at room temperature (25℃) at a rate of 1C, the capacity retention rate is still 97.56%. After 1000 cycles at -30℃ at a rate of 1C, the capacity retention rate is 53.82%.

[0087] When the phase change electrolyte in this example is applied to a lithium ion battery, the internal and external temperatures of the battery do not exceed 100℃ during charging and discharging; by controlling the external temperature to reach 150℃ (phase change temperature), the electrolyte changes from a liquid state to a solid state, i.e., the crosslinking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the transmission of Li + , thereby effectively preventing safety problems in the battery. During the needle puncture experiment, the temperature of the punctured part increases rapidly, and the local electrolyte also changes from a liquid state to a solid state, preventing the spread of heat diffusion.

[0088] Example 5

[0089] The phase change electrolyte provided in this example is composed of the following components:

[0090] Lithium salt: 2 mol / L of LiPF6, solvent: a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, crosslinking agent: 2 wt% of pentaerythritol tetraacrylate (PETTA), 2 wt% of TiO2 nanoparticles.

[0091] The preparation method of the phase change electrolyte is the same as that in Example 1.

[0092] The ionic conductivity of the phase change electrolyte in the liquid state in this example is 1.5 x 10 -2 S cm -1 When heated to 150℃, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm-1 , completely blocking Li + transport.

[0093] The phase change electrolyte is used in a button lithium battery with lithium iron phosphate as the positive electrode, and the preparation method of the battery is the same as in Example 1.

[0094] After standing and formation, the capacity of the tested battery is 5 Ah. After 1000 cycles at room temperature (25℃) at a rate of 1C, the capacity retention rate is 94.62%. After 1000 cycles at-30℃ at a rate of 1C, the capacity retention rate is 63.45%.

[0095] When the phase change electrolyte of the present example is applied to a lithium ion battery, the temperature inside and outside the battery does not exceed 100℃ during the charging and discharging processes; by controlling the external temperature to 150℃ (phase change temperature), the electrolyte changes from a liquid state to a solid state, i.e., the crosslinking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking Li + transport, thereby effectively preventing safety problems of the battery. During the needle puncture experiment, the temperature at the punctured part increases rapidly, and the local electrolyte also changes from a liquid state to a solid state, preventing the spread of heat diffusion.

[0096] Example 6

[0097] The phase change electrolyte provided in the present example is composed of the following components:

[0098] Lithium salt: 2 mol / L of LiPF6, solvent: a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, crosslinking agent: 1.5 wt% of polydimethylsiloxane (PDMS) and 1.5 wt% of SiO2 nanoparticles, additive: 2 wt% of fluoroethylene carbonate (FEC).

[0099] The preparation method of the phase change electrolyte is the same as in Example 1.

[0100] The ionic conductivity of the phase change electrolyte of the present example in a liquid state is 1.0×10 -2 S cm -1 When heated to 160℃, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking Li + transport.

[0101] The phase change electrolyte is used in a button lithium battery with lithium iron phosphate as the positive electrode, and the preparation method of the battery is the same as in Example 1.

[0102] After resting and forming, the battery's capacity was tested to 5Ah. After 1000 cycles at a 1C rate at room temperature (25°C), the battery retained 89.5% of its capacity. After 1000 cycles at a 1C rate at -30°C, the capacity retention was 85.67%.

[0103] When the phase-change electrolyte of this embodiment is applied to a lithium-ion battery, the temperature inside and outside the battery does not exceed 100°C during charging and discharging. When the external temperature is controlled to reach 160°C (phase-change temperature), the electrolyte changes from liquid to solid, i.e., the cross-linking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity drops to <0.01 mS cm -1 , completely blocking Li + During the needle penetration test, as the temperature of the punctured area rises rapidly, the local electrolyte also changes from liquid to solid, preventing the spread of heat diffusion.

[0104] Example 7

[0105] This embodiment provides a phase change electrolyte composed of the following components:

[0106] Lithium salt: 2 mol / L LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1, crosslinker: 3 wt% polydimethylsiloxane (PDMS), 2 wt% SiO2 nanoparticles, additive: 1 wt% fluoroethylene carbonate (FEC).

[0107] The preparation method of the phase change electrolyte is the same as that in Example 1.

[0108] The ionic conductivity of the phase change electrolyte in this embodiment is 1.2×10 -2 S cm -1 When heated to 160°C, the electrolyte viscosity increases sharply (>1000 Pa·s) and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking Li + transmission.

[0109] The phase change electrolyte is used in a button-type lithium battery with lithium iron phosphate as the positive electrode. The preparation method of the battery is the same as that of Example 1.

[0110] After resting and forming, the battery's capacity was measured at 5Ah. After 1000 cycles at a 1C rate at room temperature (25°C), the battery retained 88.8% of its capacity. After 1000 cycles at a 1C rate at -30°C, the capacity retention was 84.43%.

[0111] When the phase change electrolyte of the embodiment is applied to a lithium ion battery, the temperature inside and outside the battery does not exceed 100℃ during charging and discharging; by controlling the external temperature to reach 160℃ (phase change temperature), the electrolyte changes from liquid to solid, i.e. the crosslinking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the transmission of Li + , thereby effectively preventing safety problems of the battery. During the needle puncture experiment, the temperature at the punctured part rises rapidly, and the local electrolyte also changes from liquid to solid, preventing the spread of heat diffusion.

[0112] Example 8

[0113] The phase change electrolyte provided in the embodiment is composed of the following components:

[0114] Lithium salt: 2 mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1 to form, crosslinking agent: 3wt% polydimethylsiloxane (PDMS), 2wt% TiO2 nanoparticles, additive: 1wt% fluoroethylene carbonate (FEC).

[0115] The preparation method of the phase change electrolyte is the same as that of Example 1.

[0116] The ionic conductivity of the phase change electrolyte of the embodiment in liquid state is 1.4×10 -2 S cm -1 When heated to 160℃, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the transmission of Li + .

[0117] The phase change electrolyte is used in a button lithium battery with lithium iron phosphate as the positive electrode, and the preparation method of the battery is the same as that of Example 1.

[0118] After standing and formation, the capacity of the tested battery is 5 Ah. After 1000 cycles at room temperature (25℃) at a rate of 1C, the capacity retention rate is still 90.76%. After 1000 cycles at -30℃ at a rate of 1C, the capacity retention rate is 82.34%.

[0119] When the phase change electrolyte of the embodiment is applied to a lithium ion battery, the temperature inside and outside the battery does not exceed 100℃ during charging and discharging; by controlling the external temperature to reach 160℃ (phase change temperature), the electrolyte changes from liquid to solid, i.e. the crosslinking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm-1 , the Li + transport is completely blocked, and the battery safety problem is effectively suppressed. In the process of the needle-penetration experiment, the temperature of the penetrated part rapidly increases, and the local electrolyte also changes from liquid to solid, preventing the spread of heat diffusion.

[0120] Example 9

[0121] The phase-change electrolyte provided in this example is composed of the following components:

[0122] Lithium salt: 2 mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1, cross-linking agent: 2 wt% of polyethylene glycol diacrylate (PEGDA), 2 wt% of SiO2 nanoparticles, additive: 1.5 wt% of vinyl sulfate (DTD).

[0123] The preparation method of the phase-change electrolyte is the same as that in Example 1.

[0124] The ionic conductivity of the phase-change electrolyte in the liquid state is 3.0 x 10 -2 S cm -1 . When heated to 150°C, the viscosity of the electrolyte rapidly increases (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the Li + transport.

[0125] The phase-change electrolyte is used in a button lithium battery with lithium iron phosphate as the positive electrode, and the preparation method of the battery is the same as that in Example 1.

[0126] After standing and formation, the test battery capacity is 5 Ah. After 1000 cycles at room temperature (25°C) at a rate of 1C, the capacity retention rate is still 98.5%. After 1000 cycles at -30°C at a rate of 1C, the capacity retention rate is 87.3%.

[0127] When the phase-change electrolyte of this example is applied to a lithium ion battery, the internal and external temperatures of the battery do not exceed 100°C during the charging and discharging processes; by controlling the external temperature to reach 150°C (the phase-change temperature), the electrolyte changes from liquid to solid, i.e., the cross-linking agent forms a three-dimensional network, the viscosity of the electrolyte rapidly increases (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the Li + transport, thereby effectively suppressing the battery safety problem. In the process of the needle-penetration experiment, the temperature of the penetrated part rapidly increases, and the local electrolyte also changes from liquid to solid, preventing the spread of heat diffusion.

[0128] Example 10

[0129] The phase change electrolyte provided by the embodiment is composed of the following components:

[0130] Lithium salt: 2 mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1 to form, cross-linking agent: 2wt% of pentaerythritol tetraacrylate (PETTA), 2wt% of SiO2 nanoparticles, additive: 1.5wt% of methyl propionate (MP).

[0131] The preparation method of the phase change electrolyte is the same as that in Example 1.

[0132] The ionic conductivity of the phase change electrolyte of the embodiment is 1.8 x 10 -2 S cm -1 When heated to 150°C, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the transmission of Li + .

[0133] The phase change electrolyte is used in a button lithium battery with lithium iron phosphate as the positive electrode, and the preparation method of the battery is the same as that in Example 1.

[0134] After standing and formation, the test battery capacity is 5 Ah. After 1000 cycles at room temperature (25°C) at a rate of 1C, the capacity retention rate is still 98.1%. After 1000 cycles at -30°C at a rate of 1C, the capacity retention rate is 78.6%.

[0135] When the phase change electrolyte of the embodiment is applied to a lithium ion battery, the internal and external temperatures of the battery do not exceed 100°C during charging and discharging; by controlling the external temperature to 150°C (phase change temperature), the electrolyte changes from a liquid state to a solid state, i.e., the cross-linking agent forms a three-dimensional network, the viscosity of the electrolyte increases sharply (>1000 Pa·s), and the ionic conductivity decreases to <0.01 mS cm -1 , completely blocking the transmission of Li + , thereby effectively preventing the safety problems of the battery. During the needle puncture experiment, the temperature of the punctured part rises rapidly, and the local electrolyte also changes from a liquid state to a solid state, preventing the spread of heat diffusion.

[0136] Comparative Example 1

[0137] The electrolyte provided by Comparative Example 1 is composed of the following components:

[0138] Lithium salt: 2 mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1 to form.

[0139] The preparation method of the phase change electrolyte is as follows: in a glove box without water and oxygen, 10 ml of liquid EC is first taken into a 50 ml glass vial by a pipette, and then 10 ml of DMC is added, and mixed uniformly by mechanical stirring at 300 rpm. Then, an appropriate amount of LiPF6 is weighed and slowly added into the above mixed solvent, and continuously stirred for 6 hours under magnetic stirring to make LiPF6 completely dissolved to form a uniform and clear solution. Finally, the solution is first filtered by a filter with a pore size of 1 μm to remove large particle impurities, and then filtered by a precision filter with a pore size of 0.1 μm to obtain a pure phase change electrolyte.

[0140] The ionic conductivity of the electrolyte in the liquid state is 3.8 x 10 -3 S cm -1 No phase change upon heating.

[0141] A button lithium battery is prepared by the method of Example 1, and after standing and formation, the battery capacity is tested to be 5 Ah. After 1000 cycles at room temperature (25°C) at a rate of 1C, the battery has a capacity retention rate of 65.5%. After 1000 cycles at -30°C at a rate of 1C, the capacity retention rate is 0.12%.

[0142] When the electrolyte is applied to a lithium ion battery, during the needle puncture experiment, the temperature of the punctured part rapidly increases, and the electrolyte does not turn into a solid state.

[0143] Comparative Example 2

[0144] The electrolyte provided in Comparative Example 2 is composed of the following components:

[0145] Lithium salt: 2 mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed in a volume ratio of 1:1 to form, 2 wt% SiO2 nanoparticles.

[0146] The preparation method of the phase change electrolyte is as follows: in a glove box without water and oxygen, 10 ml of liquid EC is first taken into a 50 ml glass vial by a pipette, and then 10 ml of DMC is added, and mixed uniformly by mechanical stirring at 300 rpm. Then, an appropriate amount of LiPF6 is weighed and slowly added into the above mixed solvent, and continuously stirred for 6 hours under magnetic stirring to make LiPF6 completely dissolved to form a uniform and clear solution. Then, an appropriate amount of SiO2 nanoparticles is added, and mechanical stirring is continued for 4 hours to ensure that the components are fully and uniformly dispersed. Finally, the solution is first filtered by a filter with a pore size of 1 μm to remove large particle impurities, and then filtered by a precision filter with a pore size of 0.1 μm to obtain a pure phase change electrolyte.

[0147] The ionic conductivity of the electrolyte in the liquid state is 4.7 x 10 -3 S cm-1 No phase change upon heating.

[0148] A button lithium battery was prepared by the same method as in Example 1. After standing and formation, the battery capacity was tested to be 5 Ah. After 1000 cycles at room temperature (25°C) at a rate of 1C, the battery had a capacity retention rate of 72.3%. After 1000 cycles at -30°C at a rate of 1C, the capacity retention rate was 0.45%.

[0149] When the electrolyte was applied to a lithium ion battery, during the needle test, the temperature of the punctured part rapidly increased, and the electrolyte did not turn into a solid state.

[0150] Comparative Example 3

[0151] The electrolyte provided in Comparative Example 3 was composed of the following components:

[0152] Lithium salt: 2 mol / L of LiPF6, solvent: ethylene carbonate (EC) and dimethyl carbonate (DMC) mixed at a volume ratio of 1:1, cross-linking agent: 2 wt% of polydimethylsiloxane (PDMS).

[0153] The preparation method of the phase change electrolyte was as follows: in an anhydrous and oxygen-free glove box, 10 ml of liquid EC was first taken out with a pipette into a 50 ml glass vial, and then 10 ml of DMC was added. The mixture was uniformly stirred at 300 rpm. Then, an appropriate amount of LiPF6 was weighed and slowly added to the above-mentioned mixed solvent. Under magnetic stirring, the stirring was continued for 6 hours to make the LiPF6 completely dissolved to form a uniform and clear solution. Then, an appropriate amount of PDMS was added, and the mechanical stirring was continued for 4 hours to ensure that the components were fully and uniformly dispersed. Finally, the mixture was first filtered using a filter with a pore size of 1 μm to remove large particle impurities, and then filtered through a precision filter with a pore size of 0.1 μm to obtain a pure phase change electrolyte.

[0154] The ionic conductivity of the electrolyte in the liquid state was 4.2 x 10 -3 S cm -1 No phase change upon heating.

[0155] A button lithium battery was prepared by the same method as in Example 1. After standing and formation, the battery capacity was tested to be 5 Ah. After 1000 cycles at room temperature (25°C) at a rate of 1C, the battery had a capacity retention rate of 68.7%. After 1000 cycles at -30°C at a rate of 1C, the capacity retention rate was 10.17%.

[0156] When the electrolyte was applied to a lithium ion battery, during the needle test, the temperature of the punctured part rapidly increased, and the electrolyte did not turn into a solid state.

[0157] From the experimental structure of Comparative Example 2 and Comparative Example 3, it can be seen that the simultaneous presence of the crosslinking agent and the inorganic nanoparticles is a key factor for the crosslinking reaction and phase change, and the absence of either of them cannot achieve phase change.

[0158] Aspects, embodiments, features of the present application are to be considered illustrative only and not restrictive in all aspects. The scope of the present application is defined only by the claims. Other embodiments, modifications, and uses thereof will be apparent to those skilled in the art, without departing from the spirit and scope of the claimed application.

[0159] In the preparation method of the present application, the order of each step is not limited to the listed order, and for those skilled in the art, the order of each step can be changed without creative labor, which is within the protection scope of the present application. In addition, two or more steps or actions can be performed simultaneously.

[0160] Finally, it should be noted that the specific embodiments described herein are merely illustrative of the present application and are not intended to limit the embodiments of the present application. Those skilled in the art can make various modifications or supplements to the described specific embodiments or replace them with similar ways. Here, it is not necessary or possible to fully exemplify all embodiments. However, any obvious changes or variations derived from the spirit of the present application are still within the protection scope of the present application, and any additional limitations are contrary to the spirit of the present application.

Claims

1. A composite phase change electrolyte, characterized by, The lithium salt, solvent, cross-linking agent, inorganic nanoparticles; the adding amount of cross-linking agent, inorganic nanoparticles is respectively independently 0.1-10wt% of total electrolyte; The cross-linking agent is one or more of polysiloxane derivatives, multifunctional acrylate derivatives.

2. The composite phase change electrolyte according to claim 1, wherein The polysiloxane derivatives are one or more of polydimethylsiloxane, polymethylvinylsiloxane, polymethylphenylsiloxane; And / or, the multifunctional acrylate derivatives are pentaerythritol tetraacrylate or polyethylene glycol diacrylate; And / or, the inorganic nanoparticles are one or more of silicon dioxide, titanium dioxide, zinc oxide, zirconium oxide, magnesium oxide, niobium dioxide; And / or, the lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluoro oxalate borate, lithium bis-trifluoromethanesulfonimide, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide; And / or, the concentration of lithium salt is 0.1-5mol / L; And / or, the solvent is one or more of carbonate solvents, ether solvents.

3. The composite phase change electrolyte of claim 1, wherein The adding amount of cross-linking agent is 0.5-5wt% of total electrolyte, and the adding amount of inorganic nanoparticles is 0.5-5wt% of total electrolyte.

4. The composite phase change electrolyte according to claim 1 or 2, wherein The cross-linking agent is polyethylene glycol diacrylate, and the inorganic nanoparticles are silicon dioxide.

5. The composite phase change electrolyte of claim 1, wherein The electrolyte further comprises an additive, and the additive is one or more of ethyl acetate, methyl propionate, fluorinated ethylene carbonate, vinylene carbonate, vinyl sulfate, 1,3-propane sultone; The adding amount of additive is 0.1-5wt% of total electrolyte.

6. The composite phase change electrolyte of claim 1, wherein The ionic conductivity of the electrolyte in the liquid state is 4*10 -3 ~ 5*10 -2 S cm -1 -1 . The phase transition temperature of the electrolyte is 140-180°C. When the phase transition temperature is triggered, the electrolyte changes from liquid to solid. At this time, the electrolyte viscosity is greater than 1000 Pa·s and the ionic conductivity is less than 0.01mS cm -1 .

7. The method for preparing a composite phase-change electrolyte according to claim 1, wherein: The method comprises the following steps: The lithium salt is added to the solvent, and stirred and mixed for 0.5-10h until the solid is dissolved; then the cross-linking agent and inorganic nanoparticles are added and stirred and mixed for 0.5-10h; and the electrolyte is obtained by filtration.

8. A lithium-ion battery, characterized by The method comprises a positive electrode sheet, a negative electrode sheet, and an electrolyte, wherein the electrolyte is the composite phase change type electrolyte according to claim 1.

9. The lithium-ion battery of claim 8, wherein, The positive electrode sheet comprises a current collector and a positive electrode material on the current collector; the positive electrode material comprises 70-99wt% of positive electrode active material, 0.5-10wt% of binder, and 0.5-20wt% of conductive agent; The negative electrode sheet comprises a current collector and a negative electrode material on the current collector; the negative electrode material comprises 70-99wt% of negative electrode active material, 0.5-10wt% of binder, and 0.5-20wt% of conductive agent.

10. The lithium-ion battery of claim 8, wherein, The positive electrode active material is one or more of lithium iron phosphate, lithium cobaltate, lithium manganate, ternary lithium, and lithium sulfur; And / or, the negative electrode active material is one or more of graphite, soft carbon, hard carbon, silicon-based, lithium titanate, and titanium niobate; And / or, the binder comprises one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene butadiene rubber, guar gum, sodium alginate, polyacrylic acid, and chitosan; And / or, the conductive agent comprises one or more of acetylene black, carbon nanotubes, and graphene.

Citation Information

Patent Citations

  • Organic phase-change electrolyte and application thereof

    CN113258134A

Cited By

  • Electrolyte and battery comprising same

    CN122267304A